(untitled) (Dissertare, 2022)
This article focuses on the fact that Foreign Direct Investment (FDI) is a strategic factor in Costa Rica’s trade policy and its economic and social development plan. That is why, the general objective focused on conducting a prospective analysis of FDI with a horizon of 2030, an approach that leads to a public policy design process with a long-term vision. Methodologically, it was based on a qualitative research approach, with an action-research design. For the prospective analysis, several experts participated who offered their support to obtain the pertinent results. The prospective analysis covered three phases: obtaining basic information, design of scenarios and a vision for the future. With the processed information, a "Bet Scenario" was defined, in which Costa Rica is expected to maintain an economic development model based on activities for the production of value-added goods and services, with an increasingly diversified export offer and a favorable business climate, which allows it to compete as an increasingly integrated global commercial actor, both in attractiveness for FDI, as well as its effective insertion in value chains. Based on this scenario, public policy guidelines were proposed to attract foreign direct investment in the country with a view to the year 2030.